Is aberrant affective cognition an endophenotype for affective disorders? A monozygotic twin study - Meluken, I; Ottesen, N; Harmer, C; Scheike, T; Kessing, L; Vinberg, M; Miskowiak, K (Cambridge University Press, 2018)
Background Identification of endophenotypes can improve prevention, detection and development of new treatments. We therefore investigated whether aberrant affective cognition constitutes an endophenotype for affective disorders by being present in monozygotic (MZ) twins with unipolar or bipolar disorder in partial remission (i.e. affected) and their unaffected co-twins (i.e. high-risk) relative to twins with no family history of affective disorder (i.e. low-risk). Methods We conducted an assessor blind cross-sectional study from 2014–2017 of MZ twins using Danish population-based registers in recruitment. Twins attended one test session involving neurocognitive testing, clinical ratings and questionnaires. Main outcomes were attention to and recognition of emotional facial expressions, memory of emotional self-referential words, emotion regulation and coping strategies. Results Participants were 103 affected, 44 high-risk and 36 low-risk MZ twins. Groups were demographically well-balanced and showed comparable non-affective cognitive performance. We observed no aberrant affective cognition in affected and high-risk relative to low-risk twins. However, high-risk twins displayed attentional avoidance of emotional faces (Ps ≤ .009) and more use of task-oriented coping strategies (P = .01) compared with affected twins. In contrast affected twins showed more emotion-oriented coping than high- and low-risk twins (Ps ≤ .004). Conclusion Our findings provide no support of aberrant affective cognition as an endophenotype for affective disorders. High-risk twins’ attentional avoidance of emotional faces and greater use of task-oriented coping strategies may reflect compensatory mechanisms.